MAYBE Initial complexity problem: 1: T: (1, 1) f0(a) -> f1(b) [ b >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b) [ b >= 2 ] with all transitions in problem 1, the following new transition is obtained: f0(a) -> f1(b') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 ] We thus obtain the following problem: 2: T: (1, 2) f0(a) -> f1(b') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 ] with all transitions in problem 2, the following new transition is obtained: f0(a) -> f1(b'') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 ] We thus obtain the following problem: 3: T: (1, 3) f0(a) -> f1(b'') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 ] with all transitions in problem 3, the following new transition is obtained: f0(a) -> f1(b''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 ] We thus obtain the following problem: 4: T: (1, 4) f0(a) -> f1(b''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 ] with all transitions in problem 4, the following new transition is obtained: f0(a) -> f1(b'''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 ] We thus obtain the following problem: 5: T: (1, 5) f0(a) -> f1(b'''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 ] with all transitions in problem 5, the following new transition is obtained: f0(a) -> f1(b''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 ] We thus obtain the following problem: 6: T: (1, 6) f0(a) -> f1(b''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 ] with all transitions in problem 6, the following new transition is obtained: f0(a) -> f1(b'''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 ] We thus obtain the following problem: 7: T: (1, 7) f0(a) -> f1(b'''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 ] with all transitions in problem 7, the following new transition is obtained: f0(a) -> f1(b''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 ] We thus obtain the following problem: 8: T: (1, 8) f0(a) -> f1(b''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 ] with all transitions in problem 8, the following new transition is obtained: f0(a) -> f1(b'''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 ] We thus obtain the following problem: 9: T: (1, 9) f0(a) -> f1(b'''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 ] with all transitions in problem 9, the following new transition is obtained: f0(a) -> f1(b''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 ] We thus obtain the following problem: 10: T: (1, 10) f0(a) -> f1(b''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 ] with all transitions in problem 10, the following new transition is obtained: f0(a) -> f1(b'''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 ] We thus obtain the following problem: 11: T: (1, 11) f0(a) -> f1(b'''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 ] with all transitions in problem 11, the following new transition is obtained: f0(a) -> f1(b''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 ] We thus obtain the following problem: 12: T: (1, 12) f0(a) -> f1(b''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 ] with all transitions in problem 12, the following new transition is obtained: f0(a) -> f1(b'''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 ] We thus obtain the following problem: 13: T: (1, 13) f0(a) -> f1(b'''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 ] with all transitions in problem 13, the following new transition is obtained: f0(a) -> f1(b''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 ] We thus obtain the following problem: 14: T: (1, 14) f0(a) -> f1(b''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 ] with all transitions in problem 14, the following new transition is obtained: f0(a) -> f1(b'''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 /\ 1 >= b'''''''''''''' /\ b'''''''''''''' + 1 >= 0 /\ c''''''''''''' >= 2 ] We thus obtain the following problem: 15: T: (1, 15) f0(a) -> f1(b'''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 /\ 1 >= b'''''''''''''' /\ b'''''''''''''' + 1 >= 0 /\ c''''''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(b'''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 /\ 1 >= b'''''''''''''' /\ b'''''''''''''' + 1 >= 0 /\ c''''''''''''' >= 2 ] with all transitions in problem 15, the following new transition is obtained: f0(a) -> f1(b''''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 /\ 1 >= b'''''''''''''' /\ b'''''''''''''' + 1 >= 0 /\ c''''''''''''' >= 2 /\ 1 >= b''''''''''''''' /\ b''''''''''''''' + 1 >= 0 /\ c'''''''''''''' >= 2 ] We thus obtain the following problem: 16: T: (1, 16) f0(a) -> f1(b''''''''''''''') [ b >= 2 /\ 1 >= b' /\ b' + 1 >= 0 /\ c >= 2 /\ 1 >= b'' /\ b'' + 1 >= 0 /\ c' >= 2 /\ 1 >= b''' /\ b''' + 1 >= 0 /\ c'' >= 2 /\ 1 >= b'''' /\ b'''' + 1 >= 0 /\ c''' >= 2 /\ 1 >= b''''' /\ b''''' + 1 >= 0 /\ c'''' >= 2 /\ 1 >= b'''''' /\ b'''''' + 1 >= 0 /\ c''''' >= 2 /\ 1 >= b''''''' /\ b''''''' + 1 >= 0 /\ c'''''' >= 2 /\ 1 >= b'''''''' /\ b'''''''' + 1 >= 0 /\ c''''''' >= 2 /\ 1 >= b''''''''' /\ b''''''''' + 1 >= 0 /\ c'''''''' >= 2 /\ 1 >= b'''''''''' /\ b'''''''''' + 1 >= 0 /\ c''''''''' >= 2 /\ 1 >= b''''''''''' /\ b''''''''''' + 1 >= 0 /\ c'''''''''' >= 2 /\ 1 >= b'''''''''''' /\ b'''''''''''' + 1 >= 0 /\ c''''''''''' >= 2 /\ 1 >= b''''''''''''' /\ b''''''''''''' + 1 >= 0 /\ c'''''''''''' >= 2 /\ 1 >= b'''''''''''''' /\ b'''''''''''''' + 1 >= 0 /\ c''''''''''''' >= 2 /\ 1 >= b''''''''''''''' /\ b''''''''''''''' + 1 >= 0 /\ c'''''''''''''' >= 2 ] (?, 1) f1(a) -> f1(b) [ 1 >= b /\ b + 1 >= 0 /\ c >= 2 ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 1.126 sec (SMT: 1.031 sec)